EXPLORING VOCABULARY ENRICHMENT AN EXPERIMENTAL INVESTIGATION USING THE TIKTOK SOCIAL MEDIA PLATFORM - Ramadani, Mahruji Robiatu (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This experimental study investigates the possibility of using Antonio Parlati's account on the social media site Tik-Tok as a useful tool to improve students' vocabulary in English. Pre-tests, mid-tests, and post-tests are used in a quasi-experimental design to examine how Tik-Tok affects vocabulary development. Through his Tik-Tok films, Italian content creator Antonio Parlati, who specializes in English language acquisition, offers insightful lexical content. The study involves 20 students of X grade class, ages 15 to 17, and the Tik-Tok App Knowledge Test is used for evaluation. The findings show that individuals' vocabulary learning has improved to differing degrees; terms like "Also" are simple to learn, while words like "This essay talks about" present difficulties. The study emphasizes Antonio Parlati's distinct teaching style, Tik-Tok's worldwide appeal, and its dynamic learning environment. In the end, the study finds that Tik-Tok can be a useful and entertaining tool for vocabulary enrichment when utilized carefully, which can improve language learning results.